Racial and Linguistic prejudice in Brazil: comparisons, contrasts and anthropophagic solutions. - Paul O’neill (Revista Falange Miúda, 2023)
In this article I compare and contrast how prejudicial views about race have/have not intersected with prejudicial views about Language in the history of Brazil. I examine both within Latin American discussions related to civilisation and barbarism, onto which the distinction between Educated and Popular Brazilian Portuguese maps. I focus on the work of the modernist Anthropophagic Movement and how this movement combined with subsequent developments helped to break the dichotomy civilisation/barbarism and redefine Brazilian identity and place at its centre mixed-race characteristics. I suggest that a similar movement is necessary to overcome the prejudices against popular Brazilian Portuguese.